Model to Evaluate Hierarchical Organizations Performance in Implementing Higher Education Information Systems - Reni Haerani; Titik Khawa Abdul Rahman (Research Synergy Foundation, 2024)
Adopting and successfully implementing information systems in higher education is essential for improving administrative processes and communication and supporting academic activities. However, the hierarchical nature of such organizations poses unique challenges that must be addressed for the effective adoption of information systems. This study proposes a framework to assess the performance of hierarchical organizations in effectively implementing information systems in universities. The proposed framework evaluates various dimensions that influence the successful adoption of information systems in hierarchical organizations. This dimension includes leadership support, communication channels, organizational culture, and resource allocation. The conceptual framework provides a holistic assessment of an institution’s ability to effectively adopt and utilize information systems. A structural equation model and Smart Partial Least Squares (Smart PLS) were used for data analysis. Using a sample of 121 respondents, data were collected using a questionnaire instrument using the Google Form link at Banten Province higher education leadership levels. This framework provides a structured approach to assessing the performance of hierarchical organizations in terms of the adoption of information system success in higher education institutions. By leveraging this framework, institutions can enhance their information system adoption processes and ultimately improve their effectiveness in using information systems for academic and administrative purposes. The results indicate that hierarchical organizations can optimize performance when implementing higher education information systems, focusing not only on the technical aspects of the system but also on organizational culture, communication, and leadership involvement.